Functional implications for the microtubule-associated protein tau: localization in oligodendrocytes. - LoPresti, P (1995)
We present evidence that the microtubule-associated protein tau is present in oligodendrocytes (OLGs), the central nervous system cells that make myelin. By showing that tau is distributed in a pattern similar to that of myelin basic protein, our results suggest a possible involvement of tau in some aspect of myelination. Tau protein has been identified in OLGs in situ and in vitro. In interfascicular OLGs, tau localization, revealed by monoclonal antibody Tau-5, was confined to the cell somata. However, in cultured ovine OLGs with an exuberant network of processes, tau was detected in cell somata, cellular processes, and membrane expansions at the tips of these processes. Moreover, in such cultures, tau appeared localized adjacent to or coincident with myelin basic protein in membrane expansions along and at the ends of the cellular processes. The presence of tau mRNA was documented using fluorescence in situ hybridization. The distribution of the tau mRNA was similar to that of the tau protein. Western blot analysis of cultured OLGs showed the presence of many tau isoforms. Together, these results demonstrate that tau is a genuine oligodendrocyte protein and pave the way for determining its functional role in these cells.